Why do you want to be a mathematics teacher? Stories “in the middle" - Pocalana, Gabriella; Liljedahl, Peter (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
This paper aims at studying the affective aspects of the relationship with mathematics of prospective middle school mathematics teachers, enrolled in a master’s degree in Natural Sciences focused on secondary mathematics and science education. According to the principles of narrative data collection, the 10 prospective teachers of our sample have been asked to answer two open prompts: “Me and maths” and “Me as a maths teacher”. Data analysis has been conducted according to the dimensions holistic vs categorical and content vs form. The results reveal that the participants’ relationship with mathematics, as well as their grades, can be described as fluctuating. Their motivations to become mathematics teachers are not very strong, but they declared a marked willingness to empathize with their future students’ difficulties in mathematics.